2015
DOI: 10.5194/hessd-12-7127-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SPARSE model for the prediction of water stress and evapotranspiration components from thermal infra-red data and its evaluation over irrigated and rainfed wheat

Abstract: Abstract. Evapotranspiration is an important component of the water cycle, especially in semi-arid lands. A way to quantify the spatial distribution of evapotranspiration and water stress from remote-sensing data is to exploit the available surface temperature as a signature of the surface energy balance. Remotely sensed energy balance models enable to estimate stress levels and, in turn, the water status of continental surfaces. Dual-source models are particularly useful since they allow deriving a rough esti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These good performances are in agreement with results reported in the literature. Indeed, several studies showed that the estimation of R n by SVAT models is good on several type of canopy , Boulet et al, 2015and 2009a. The most important differences are encountered on the Agdal site and can be explained by the slight overestimation (not shown) of the infrared radiation (LW up ) by ISBA-2P for both seasons (Bias=13.7 and 12.7 420 W/m 2 for the 2003 and 2004 seasons, respectively).…”
Section: Other Components Of the Energy Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…These good performances are in agreement with results reported in the literature. Indeed, several studies showed that the estimation of R n by SVAT models is good on several type of canopy , Boulet et al, 2015and 2009a. The most important differences are encountered on the Agdal site and can be explained by the slight overestimation (not shown) of the infrared radiation (LW up ) by ISBA-2P for both seasons (Bias=13.7 and 12.7 420 W/m 2 for the 2003 and 2004 seasons, respectively).…”
Section: Other Components Of the Energy Budgetmentioning
confidence: 99%
“…The representation of the intensity of this coupling, and ultimately the performance of the models to reproduce the ET and its partition, is directly related to the structure adopted in the model (single-or dual-source). In particular, it has been shown that a more realistic representation of the energy balance and a better representation of the respective contributions of E and T r to ET (Shuttleworth and Wallace, 1985;Norman et al, 1995;Béziat et al, 2013;Boulet et al, 2015) could be obtained by solving several separate 95 energy balances for each of the sources. In this context, two types of dual-source models were developed (Lhomme et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, improvements in computational performance, open-source programming languages, lower data requirements, and the simplification of different complex approaches used to estimate actual crop evapotranspiration (ET a ) through RS have contributed, at least in part, to reducing the existing gap between RS physical modeling methods and agricultural applications. Among the different methods, the surface energy balance (SEB) models are probably the most complex to run, but at the same time provide high accuracy and robustness in estimating ET a in different environments ( Norman et al, 1995 ; Bastiaanssen et al, 1998 ; Mecikalski et al, 1999 ; Allen et al, 2007 ; Boulet et al, 2015 ). These models have mostly been used for assessing the spatial and temporal variability of ET a at regional and field scale using satellite imagery ( Semmens et al, 2016 ; He et al, 2017 ; Knipper et al, 2019 ), although some of them have also been used with very high-resolution aircraft imagery ( Hoffman et al, 2016 ; Xia et al, 2016 ; Nieto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%